Kompetensi Manajerial Kepala Madrasah di MTs Al-Hikmah Palembang - Ibrahim Ibrahim (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2018)
The topic of this study was the managerial competence of principle of madrasahat MTs Al-Hikmah Palembang. The undelying rationale was the role of madrasah princplein an educational institution was very important, MTs Al-Hikmah which was located in adensely populated society, demanded the principle to be able to manage his institution inachieving educational goals. The scope ranging from the preparation of school plans,school organizations to supervision of the i school activities implimentation. This researchwas field research that was qualitative naturalistic. and the sources of the data wereprimary data and secondary data. the technique for collcting the data was using fieldobservations regarding the implementation of madrasah chief managerial competencies,then the documentation also dealt with managerial competence activities. While thisinterview was carried out to the Head of Madrasah, Educators, Administrative Staff, andseveral other respondents. Data analysis started from reduction, data presentation andverification. Based on the results of the data analysis, it was known that the managerialcompetence of the priciple had been going well, because the scope of the manager'smadrasah managerial competencies had been ranging from planning, organizing tosupervision of the madrasah activities implimntaion. it had been going well and wassupported by educators and education staff including the condusive madrasah climate. itwas just that the budget was still a problem in supporting the education process and that hadan impact in school facilities.